Analysis Of Facilities and Services of Pulogebang Integrated Terminal to Increase Passenger Interest - Oce Prasetya; Ahmad Hidayat; Lut Mafrudoh; Riza Affiat; Indriyati; Euis Saribanon (Dinasti International Journal of Digital Business Management, 2024)
Abstract: Pulogebang Integrated Terminal is one of the largest bus terminals in Jakarta which has an important role in serving community mobility. However, in recent years, passenger interest in using this terminal has decreased. Pulogebang Integrated Terminal to increase passenger interest in 2023. Analysis of Integrated Terminal Facilities and Services to Increase Passenger Interest in 2023 is a research article within the scope of the field of marketing management. The purpose of this article is to build a hypothesis of the influence between variables that will be used in further research. Research objects in online libraries, Google Scholar, Mendeley, and other academic online media.  This research method uses quantitative methods with surveys to obtain samples to be calculated, and then data tabulation and statistical calculations are carried out to test existing hypotheses. The results of this article: 1) Facilities affect increasing passenger interest, and 2) Integrated Terminal Services affect Increasing Passenger Interest.